Exploring the materials for solar cell coating for performance enhancement - Kamarudin, Muhammad Badri (2025)
Coating of solar cells is a crucial impact to enhance efficiency, service life, and environmental resettlement of photovoltaic (PV) systems. This thesis argues a critical review of 43 materials in four major groups titled solid-state, polymer electrolyte, carbon nanotube (CNT)-based, and ionic liquid-based, considered against four main performance parameters including, hydrophilicity, antimicrobial or antifouling, wide optical bandgap (Eg), and self-healing potential. The suitability of each material to improve PV cell performance in different environments is evaluated by comparing the materials. The findings indicate that although more than half of the materials exhibit more than one positive property, none of the coatings simultaneously combines the four most important functions and thus pose a notable deficiency in existing PV coating technologies. Additionally, about 63 percent of samples do not report on Eg findings, especially with CNT-based coating, which makes optical comparisons particularly difficult. Another problem outlined by the research is the lack of normative testing procedures and the overlooking of cost-effectiveness and scalability issues, which would be necessary in practice. Materials were prioritized and paired with 5 environmental conditions such as arid, tropical, urban/industrial, remote/off-grid, and wearable PV so as to determine the best fit of most ideal solutions to the environmental conditions. The candidates such as TiO2, SLIPS, AFC-3, and GG/P3HT/LiCl-4 revealed significant advantages regarding the environment of their implementation. Finally, this review leads to an effective process of evaluating and choosing the solar cell coatings, which forms the basis of the future advancements that will strike the right balance between performance, durability and usability. The results reaffirm the necessity of versatile materials and extensive testing to direct the evolution of solar technologies at the next level.